MEMAHAMKAN OPERASI BILANGAN BULAT DENGAN PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA KELAS X MM 1 SMKN I LUMAJANG - Wiwik Kusmiati (FKIP Universitas Islam Jember, 2015)
The objective of this study is to develop how the implementation of cooperative learning of STAD model can be used to improve the students’ understanding on the concept of the integer operation at class X MM 1 SMKN 1 Lumajang. The subject of this study is the tenth graders of MM 1 SMKN 1 Lumajang. In this study, the writer employed classroom action research as the research designin which the researcher carries out the cyclical procedure of the study: planning, implementing, observing, and reflecting on the action. This study was conducted in two cycles. The results shows that the students activity in cycle 1 get the score of 42,67 out of 44. It is therefore that it was categorized as “very good” score. In cycle 2, the students scored full marks, 44. In reference to the research findings, it can be concluded that cooperative learning of STAD model can help to deepen the students’ understanding on the concept of the integer operation at class X MM 1 SMKN 1 Lumajang.Keywords: STAD, cooperative learning,